A Perspective on Vietnam - Toai, Doan Van (Tufts Archival Research Center, 2005)
Volume 5, Issue 1. Winter As a student revolutionary leader in Vietnam, Doan Van Toai helped to topple the Thieu regime and set up the Communist government. However, he quickly became disillusioned with that cause and eventually was arrested in 1975 for refusing to serve on a government finance committee. Since his release from prison in 1978 Doan Van Toai has written extensively on human rights violations in Vietnam. As a Research Fellow at the Fletcher School, he is presently completing another book entitled, Vietnam: Neither Peace nor Honor. The following interview conducted by Barbara Blodi, a MALD degree candidate at the Fletcher School, touches on themes from his last work, and probes into the Vietnamese perception of the fraternal rivalry between western and eastern political ideology.